Outdoor thermal comfort and cognition impact pro-environmental behaviors: evidence from a field experiment in the tropics - Borzino, Natalia; Chng, Samuel; Schubert, Renate (Frontiers in Psychology, 2025)
IntroductionClimate change and the Urban Heat Island (UHI) effect pose a serious threat, particularly for tropical countries like Singapore, which experience high air temperatures and humidity levels and are heating up twice as fast as the global average. Policy interventions have focused on promoting individuals' engagement in pro-environmental behaviors to mitigate urban heat and CO2 emissions. Although past research highlights individuals' long-lasting environmental attitudes and awareness, these do not always translate into action. This study investigates the attitudes-behavior gap and the awareness-behavior gap from a cognitive perspective, and examines the extent to which cognition is affected by urban heat.MethodsUsing a quasi-experimental field design involving 309 older adults and a novel analytical framework, we assessed the relationship between thermal comfort, cognitive control, and pro-environmental behavior.ResultsWe found that low thermal comfort negatively affects cognitive control, which in turn significantly moderates the relationship between pro-environmental attitudes and behaviors, as well as between awareness and behaviors. Specifically, individuals with higher cognitive control capacity demonstrated a stronger moderating effect, helping to close the attitudes-behavior and awareness-behavior gaps and encouraging more pro-environmental behavior.DiscussionPolicies aimed at preserving thermal comfort and enhancing heat adaptation can support not only the health and wellbeing of senior citizens but also their pro-environmental behaviors. This presents a potentially central lever for behavioral change initiatives.